Las encrucijadas del Partido Comunista de China - Ríos, Xulio (Huarte de San Juan. Geografía e Historia, 2006)
The CCP is the key to the process of reform in China. Nearly three decades after having been initiated, the intensive transformations taken in social or economic areas give rise to the urgency of their adaptation to a new reality, with an agenda that is notable for the diverse nature of its reach. This has led to much debate regarding the final orientation of the process and the role that such a procedure should play. Despite economic liberalization, the CCP has not in any way renounced its political preeminence.